1963
DOI: 10.1126/science.139.3550.115
|View full text |Cite
|
Sign up to set email alerts
|

Paraplegic Dogs: Urinary Bladder Evacuation with Direct Electric Stimulation

Abstract: Stimulation of the detrusor muscle by means of two implanted wire electrodes increased intravesical pressure markedly in ten trials in normal dogs and in nine trials following transection of the dog's lumbar spinal cord. The urinary bladder could be completely emptied up to 2 or 3 weeks postoperatively. Later stimulation provoked an equally copious urinary flow but a residue persisted even when progressively higher voltage was applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1964
1964
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…These findings are consistent with data from the literature found after stimulation of electrodes implanted into the bladder wall by open surgery [Bradley et al, 1962[Bradley et al, , 1963Kantrowitz and Schamaun, 1963;Timm and Bradley, 19691. Simultaneous stimulations leading to contractions at the level of the pelvic floor, which could possibly be caused by current spread, are not anticipated as no elevated voiding pressures were observed.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are consistent with data from the literature found after stimulation of electrodes implanted into the bladder wall by open surgery [Bradley et al, 1962[Bradley et al, , 1963Kantrowitz and Schamaun, 1963;Timm and Bradley, 19691. Simultaneous stimulations leading to contractions at the level of the pelvic floor, which could possibly be caused by current spread, are not anticipated as no elevated voiding pressures were observed.…”
Section: Discussionsupporting
confidence: 94%
“…Some of these techniques are routinely applied in appropriate cases of urinary incontinence. Stimulation of the detrusor via electrodes implanted into the bladder wall has been described earlier [Bradley et al, 1962[Bradley et al, , 1963Kantrowitz and Schamaun, 1963;Timm and Bradley, 19691. Initiation of bladder contractions and micturition was reproducibly achieved in several experimental setups using normal -.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, FES systems targeted different anatomical sites, including the bladder wall [59], pelvic nerves [45] and sacral roots [13][14][15][16]. However, direct bladder stimulation or pelvic nerve excitation failed to yield effec-tive micturition.…”
Section: Implanted Bladder Neuroprosthesesmentioning
confidence: 99%
“…Several groups developed implanted stimulators inductively coupled to external transmitters with variations in the design, placement and number of electrodes (Bradley et al, 1962;Hald et al, 1967;Stenberg et al, 1967;Susset and Boctor, 1967;Merrill and Conway, 1974;Magasi and Simon, 1986). Initial animal experiments demonstrated that spinalized dogs were able to void regularly using the implanted stimulators without requiring additional procedures (Bradley et al, 1962;Bradley et al, 1963;Kantrowitz and Schamaun, 1963). However, results in spinal cord injury patients implanted with these stimulators were much less successful (Bradley et al, 1963;Hald et al, 1967;Stenberg et al, 1967;Susset and Boctor, 1967;Merrill and Conway, 1974).…”
Section: Bladder Wall Stimulationmentioning
confidence: 99%